PELAKSANAAN LESSON STUDY BERBASIS SEKOLAH DALAM MENINGKATKAN PROFESIONAL GURU PADA MATA PELAJARAN IPS (ILMU PENGETAHUAN SOSIAL) DI SMP NEGERI 1 JEMBER - Tohirotul Maghfiroh; Umar H.M.S (Economic Education, University of Jember, 2015)
This research was intended to know the implementation of the school based lesson study to improve the social teacher’s professional. It was done at SMP Negeri 1 Jember. The destination of this research was to describe the process of lesson study and to know the effect of lesson study toward the teacher’s pedagogic and professional competences at SMP Negeri 1 Jember. This research was a descriptive qualitative research. To determine the area of this research, the research used purposive method, that was at SMP Negeri 1 Jember. The data collection methods used inthis research was documentation, interview and observation. The result of the research showed that the process of lesson study could improve the teacher’s professional both pedagogic and professional competences. The process of lesson study that was consisted of plan, do and see had a close relationship to teacher’s improvement of pedagogic and professional competences. By doing plan, do and see of lesson study, the pedagogic competence that was the teacher’s activity in the process of planning, doing, evaluating and the learning result with the use of evaluating result and evaluating could be improved. So that the professional competence the teacher would be able to improve his mastery through material, structure, concept, the lesson mind set and be able to expand the material creatively . Based on the result from one cycle to another cycle, the teacher’s got the positive improvement that was the teacher has been able to implement do appropriately by minimize the mistake from the previous cycle.